Systematic Literature Review : Resiliensi Lansia terhadap Bencana Alam - Elvita Putri; Nurhasni Nurhasni; Maria Weni Gowasa; Aulia Aulia; Aflah Zakinov Irta (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Indonesia is known as an archipelago located on the Ring of Fire, which is the confluence of three major tectonic plates, namely Indo Australia, Eurasia and the Pacific. This causes Indonesia to be an area at risk of experiencing various kinds of natural disasters. The elderly are one of the groups of people who are most vulnerable to the high psychological impact of natural disasters. Resilience in times of crisis is an important psychological ability in individuals, especially the elderly, because it is expected to make individuals strong and able to adapt to changes in conditions that occur in their lives. elderly, because it is expected to make individuals strong and able to adapt to changes in conditions that occur well. Resilience is a personal trait that refers to positive adaptation and reducing negative influences and stressors so that individuals can improve mentally and maintain their health despite experiencing severe problems. The purpose of this study is to determine and explore various images of resilience and to find out the importance of resilience for the elderly in dealing with disasters. The method used in this research is the Systematic Literature Review (SLR) method where the literature related to the research will be analyzed and synthesized. The results and conclusions of this study are that the many types of natural disasters that occur in Indonesia make people from every group, especially the elderly, have resilience. The literature analyzed is literature published on Google Scholar, ISSN standardized and published between 2019 and 2024. The number of literature analyzed in this study was 8 literature. The results of this study are a description of the resilience of the elderly consisting of several categories / levels of resilience, things that affect resilience, how the elderly adjust, and elderly preparedness for natural disasters. In addition, this study concluded that resilience is important for the elderly to deal with natural disasters.